Windfarms, fishing and benthic recovery: Overlaps, risks and opportunities. (November 2022) - Dunkley, Frith; Solandt, Jean-Luc
Abstract: The UK is a leading nation in the development of large offshore wind energy installations (OWFs). Since 2000, the UK has installed 2610 turbines covering over 2000 km 2 of UK seas. As these sites overlap with historic fishing grounds as well as Marine Protected Areas it is important to understand the relationship between the presence of these OWFs and fishing activity to assess the extent to which OWFs could act as de facto MPAs with respect to fisheries management, providing other environmental impacts are mitigated. We assessed the extent to which the fishing activity of vessels using bottom-contacting mobile gears (trawls, dredges and demersal seines) were impacted by the construction of 12 offshore windfarms in the UK EEZ. Using publicly available Global Fishing Watch fishing effort data, we found fishing rate from vessels using bottom-towed gear was reduced by 77 % following OWF construction in 11 of the 12 sites studied. A decline in bottom-towed fishing activity was recorded in OWFs where turbines were constructed in a densely aggregated patch, and an increase in fishing activity where turbines were positioned as several distinct aggregated patches within the site. We conclude that bottom-towed fishing activity is affected by turbine layout, with OWFs likely offering some protection to the benthic environment from bottom-towed gear. We suggest this reduction in bottom-towed fishing provides space for co-location opportunities and note that consultations on domestic MPA designations should involve offshore wind stakeholders in terms of OWF 'co-location' with and 'avoidance' of MPAs.